2023
DOI: 10.1186/s12981-022-00490-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders in adolescents living with HIV in Botswana

Abstract: Background As children living with HIV transition from adolescence into adulthood, they face a considerable burden of psychiatric disorders (PDs) which may vary between the perinatally and behaviorally infected. The knowledge of the pattern of these PDs in relation to the varying needs of the adolescents living with HIV (ALWHIV) is unclear but necessary for maximizing their linkage to care and improving their quality of life in Botswana.  Aim To de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
(56 reference statements)
2
4
0
Order By: Relevance
“…This finding is consistent with a previous study which reported that immunosuppression was associated with poor emotional and behavioural outcomes [45]. In a recent study done in Botswana, HIV congenitally infected adolescents were almost four times more likely to present with externalizing disorders like ADHD which may have occurred partly due to the effect of HIV on the brain [46] or immunosuppression resulting from prolonged period of poor ART adherence [47]. Researchers have found a strong association between externalizing disorders and viral load above 400 copies [46].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with a previous study which reported that immunosuppression was associated with poor emotional and behavioural outcomes [45]. In a recent study done in Botswana, HIV congenitally infected adolescents were almost four times more likely to present with externalizing disorders like ADHD which may have occurred partly due to the effect of HIV on the brain [46] or immunosuppression resulting from prolonged period of poor ART adherence [47]. Researchers have found a strong association between externalizing disorders and viral load above 400 copies [46].…”
Section: Discussionsupporting
confidence: 92%
“…This nding is consistent with a previous study which reported that immunosuppression was associated with poor emotional and behavioural outcomes (54). In a recent study done in Botswana, HIV congenitally infected adolescents were almost four times more likely to present with externalizing disorders like ADHD which may have occurred partly due to the effect of HIV on the brain (55) or prolonged period of poor ART adherence (56). In a study by Van Rie, Harrington, Dow et al (2007) it was reported that HIV infection itself can lead to neurological sequala in children as a result of static or progressive encephalopathy which affects the development of the maturing brain (57).…”
Section: Discussionsupporting
confidence: 91%
“…In a study by Van Rie, Harrington, Dow et al (2007) it was reported that HIV infection itself can lead to neurological sequala in children as a result of static or progressive encephalopathy which affects the development of the maturing brain (57). Researchers have found a strong association between externalizing disorders and viral load above 400 copies (55). In another study children with low CD4 count <500 cells/mm 3 were more likely to develop emotional and behavioural di culties as compared to children with CD4 count >500 cells/mm 3 (p=0.015)(58).…”
Section: Discussionmentioning
confidence: 99%
“…The Socio-demographic subsection contained questions on issues such as participants’ age, religion, ethnicity, educational level and gender, and parent’s marital status. It included questions on the type and level of social support they had access to; clinical variables, such as mode of infection; age at first diagnosis (HIV), and current viral load, with other details having been reported previously [ 11 , 13 ].…”
Section: Methodsmentioning
confidence: 99%